Mobility management in wireless ATM network(pengurusan mobiliti dalam rangkaian ATM wireles) - Syed Ariffin, Sharifah Hafizah (Faculty of Electrical Engineering, 2008)
Traffic control and resource management are complex issues in wireless asynchronous transfer mode (WATM) due to broad range quality-of-services (QoS), limited bandwidth spectrum and susceptibility to error. In WATM, traffic control is essential in order to protect the network from congestion and to achieve realistic network efficiency in compliance with the QoS. Micro and pico cell sites are usually used in the WATM environment. Exchanging access point to the backbone network is thus common and this may contribute to connection rejections when channels are busy. The effect to QoS at call level is the high probability of handoff dropping if the targeted call site has no available channels. The objective of this project is to design a WATM system using virtual connection tree (VCT) architecture model that can give high QoS performance in terms of probability of call lost and handoff call drop and can provide connections of a bandwidth rate that will not jeopardize QoS requirements in terms of a bandwidth given to a connection which is not less than the set threshold bandwidth. All of these will be done in mathematical analysis. The design was initially started with a scheme called With Reserved Channel (WRC), which has reserved channels for handoff calls. A low probability of handoff dropping was obtained but a set back was found which involves the probability of new call block. Hence, an improvement had been made and it is called With Queuing and Reserved Channels (WQRC), which allows queuing of new incoming calls and reserved channels for handoff calls. Using WQRC, low probability of handoff dropping was maintained and new call blocking probability was eliminated.